VAGINAL BLEEDING IN A PREMENARCHAL GIRL CAUSED BY A HIGH-PRESSURE WATER FOUNTAIN IN A THERMAL POOL - Tjaša Tibaut; Klementina Šafar; Lidija Ouček Farkaš; Zdravko Roškar (The Society for Children with Metabolic Disorders, 2020)
Vaginal bleeding in premenarchal girls is a rare but alarming symptom that may have many different causes. Opinions differ as to when a vaginal examination should be performed under general anaesthesia together with colposcopy. The most common cause of vaginal bleeding is vul- vovaginitis, followed by traumatic injuries, which can also be caused by water sports. In this article, we present the case of a six-year-old girl with vaginal bleeding caused by a high-pressure water fountain in a thermal pool.